PENURUNAN JUMLAH ERITROSIT DARAH TEPI AKIBAT PAPARAN RADIASI SINAR X DOSIS RADIOGRAFI PERIAPIKAL - Erma N.K; Supriyadi Supriyadi (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
The purpose of this study was to evaluate the decreasing of erythrocyte cappilary blood vessel on X-ray radiation exposure with periapicale radiography dosage. This study is laboratory experimental research that used the Post-Test Control Group Design. The sample research was mus musculus, male, 3–4 month of age, 20– 25 g of weight and healthy. There were 24 mus musculus that were divided into 6 groups wich each group 6 mus musculus: the first group was used as a control group (no X-ray radiation exposure), the second group was induced with X-ray radiation with once exposure of periapicale radiography dosage. The third group was induced with X-ray radiation with six- time exposure of periapicale radiography with 1 minute of interval. The fourth group was induced with X-ray radiation with fourteen-time exposure of periapicale radiography dosage with 1 minute of interval. The source of radiation was the X-ray radiation exposure was given from dental radiography unit (thropy) : periapicale projection, 70 Kvolt voltage, 8 mA, 20 cm of Source Object Distance (SOD), adult patient type and molar region selector. The entire sample was taken hereinafter sacrificed 24 hours after radiation exposure. The observation and counting of erythrocyte using with erythrocyte counting room. The data were statistically analyzed using one-way anova at significant level (α) of 0.05. The results of this study showed that was decreasing an amount of erythrocyte cappilary blood vessel; at control group was 2,5833 million cell/mm3, at the second group was 2,4167 million cell/mm3, at the third group was 2,3500 million cell/mm3, and the fourth group was 2,0000 million cell/mm3.There was significant decreasing an amount of erythrocyte among the four groups (p < 0.05). There were decreasing an amount of erythrocyte cappilary blood vessel was caused by X-ray radiation induced from periapicale radiography